Influence of LPL, APOAIV, APOAV, APOCIII and USF1 polymorphisms in a Portuguese population with clinical diagnosis of Familial Combined Hyperlipidaemia - Santos, T. (2012)
Familial Combined Hyperlipidaemia (FCHL) is a genetic disorder characterized by highly atherogenic profile with presence of sdLDL, hyperlipidaemia (hypertriglyceridaemia and/or hypercholesterolaemia), different lipid profiles in members of the same family and high apoB levels. Some polymorphisms in several genes (LPL -93T>G/D9N, APOAIV Q360H and V13M, APOAV -1131T>C and S19W, APOCIII 3238C>G, USF1s1 and USF1s2) have been associated with higher triglycerides (TG) levels or FCHL. Hypertriglyceridaemia has been suggested by some authors as an independent risk factor for cardiovascular diseases (CVD). The purpose of the present study was to verify if these associations are valid in a Portuguese FCHL population and if the above polymorphisms also affect sdLDL concentration since these particles are formed from triglyceride-rich VLDL (VLDL1). The molecular study of the above polymorphisms was performed in 45 FCHL index patients and 116 relatives by PCR amplification and direct sequencing. Total cholesterol (TC), TG, sdLDL and apoB values were measured in automated analysers. The results were analyzed with SPSS software using t-test. It was found at least one of the described polymorphism in 69 individuals (P1) but not in 92 (P2). We verified that individuals with at least one of these alterations had not only higher TG levels, as we were expecting, but also higher levels of sdLDL (TG: P1=186,1±11,0mg/dL, P2=136,7±7,3mg/dL, p<0,001; sdLDL: P1=33,2±2,3mg/dL, P2:22,6±2,2mg/dL, p=0,002). We didn’t found any significant relation between these polymorphisms and TC (P1=233,9±9,0mg/dL, P2=218,3±6,4, p=0,311). In P1 we also found an association between TG levels and CVD (with CVD: TG=227,5±23,4mg/dL, without CVD: TG=176,5±12,2mg/dL, p=0,036) that was not present in P2 (with CVD: TG=131,4±19,2mg/dL, without CVD: TG=137,3±7,9mg/dL, p=0,984). Our results not only reinforce the idea that hypertriglyceridaemia is a risk factor for CVD as suggested by some authors but also suggest that this condition is responsible for the increase of sdLDL particles in FCHL Portuguese patients.